PENERAPAN PRINSIP EKONOMI SYARIAH PADA USAHA MIKRO KECIL DAN MENENGAH ES TEH JEMURSARI WONOCOLO SURABAYA - khurun in, karina aulia; Mareseto, Kurnia Via; Rohman, Moh. Faizur (Khazanah: Jurnal Mahasiswa, 2024)
This study describes the application of sharia economic principles in Micro, Small and Medium Enterprises (MSMEs). This business is a type of business that is growing rapidly in the current era of society, which includes various specific business fields. MSMEs have an important role in addressing the issues of unemployment and poverty. They are also the backbone of the economy that is widely run by the community, especially in the sale of iced tea in Wonocolo District, Surabaya. These MSMEs play a very important role in the Indonesian economy, especially in addressing the issues of unemployment and poverty. This study aims to explore how sharia economic principles can be applied in MSME business practices that are not only oriented towards financial gain but also sustainability and justice. The research method chosen is descriptive qualitative. Through interviews, 10 MSME actors became the research subjects. The results show that MSME players in Wonocolo Sub-district have applied sharia principles such as justice, business ethics, and social responsibility, integrated in their operations. In addition, it has been found that the application of sharia economic principles helps improve competitiveness and sustainability for entrepreneurs, as well as providing social benefits for the surrounding community. So it can be concluded that the application of Islamic economic principles can be a solution to face the challenges in an increasingly competitive and complex business world.